Between need and innovative challenge: observations on female solo self-employment. Issue 1 (14th March 2016) - Bögenhold, Dieter; Fachinger, Uwe
Abstract : Purpose: – The purpose of this study is to discuss the ongoing increase of female entrepreneurship within a broader context of influencing factors, especially within the division of work. Talk about the rise and future of self-employment must be linked to the discussion about changes in the structure of occupations, labour markets and regulations and gender. The increase of the service sector and the continuous rise of the liberal professions mirror changes within the category of self-employment. All different items are embedded into a general trend of a growing knowledge society. A fundamental question is how gender matters when investigating these trends. Do we find specific "gender patterns" or will the new chances and risks lead to a greater equality of opportunities? Is the increase of solo self-employment of females driven by the need to earn a living, or is it the result of females taking the risk, e.g., to become more economically independent? Design/methodology/approach: – The paper combines conceptual thoughts on the development of self-employment and gender within stratified modern societies with empirical reflections based on public census data for Germany. The research delves deeper into the different segments of the employment system and connects empirical findings with the theoretical discussion on professional groups in modern capitalist societies. Findings: – We learn to acknowledge that the rise of self-employment is mostly supported by the rise of micro-firms and solo self-employment, of which especially solo self-employment is a female domain. The independent liberal professions also indicate a significant revival of female labour. Originality/value: – The paper highlights the increasing expansion of self-employment and specific gender patterns within this trend.